KOMUNITAS TATO ASSOCIATION RIAU TATTOO (ART) DI PEKANBARU - Nimas Khairunissa; Achmad Hidir (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
The tattoo community is a place to interact with tattoo users or tattoo lovers who have a sense of art and love of tattoos. The tattoo community in this case is a social phenomenon that is present in the midst of modern society. In this case the social group must have the role of capital for sustainability and to achieve goals in the community. Where the role of capital must be owned by every member of the social group, namely the tattoo community. This study analyzes the activities and role of capital in the Riau Tattoo Association (ART) tattoo community in Pekanbaru. Where the roles to be discussed are Social Capital, Symbolic Capital and Cultural Capital, then to find out what tattoos mean for members of the Association Riau Tattoo(ART). The theory used in this study is Capital (Social, Symbolic and Culture) Habitus and Arena. The method used in this study is descriptive qualitative with data collection techniques namely direct observation, interviews and documentation. The sampling technique used was purposive sampling technique. Where the number of informants amounted to 6 people then divided into two parts, namely 3 founders of the tattoo community, then 3 were members of the Associaion Riau Tattoo (ART) tattoo community. From the results of these studies the Riau Tattoo Association (ART) community has positive activities / activities not only for them but also for the surrounding community. The Riau Tattoo Association (ART) tattoo community has also demonstrated the role of capital in which the Social, Symbolic and Cultural Capital possessed by each member or community itself.Keywords: Tattoos, Communities, Capital